Lived experience of patients with Long COVID: a qualitative study in the UK - Rebecca Owen; James Yates; Callum Thomas; Mark A Faghy; Francesco Ferraro; Tom Bewick; Kate Haggan; Ruth E M Ashton (BMJ Open, 2023)
Background Long COVID is a rapidly evolving global health crisis requiring interdisciplinary support strategies that incorporate the lived experience of patients. Currently, there is a paucity of research documenting the day-to-day experiences of patients living with Long COVID.Objective To explore the lived experience of Long COVID patients.Study design Longitudinal, observation study.Setting An inductive, data-driven, qualitative approach was used to evaluate hand-written diaries obtained from individuals who had been referred to a Derbyshire Long COVID clinic.Participants 12 participants (11 females, age 49±10 years, 11 Caucasians) were recruited. Participants were included if they had a previous confirmed or suspected COVID-19 infection with ongoing recovery, >18 years old, understood the study requirements and provided informed consent.Method Participants were directed to complete self-report diaries over 16 weeks. Responses were transcribed verbatim and analysed using thematic analysis.Results Three key themes were highlighted: (1) understanding who helps patients manage symptoms, (2) daily activities and the impact on quality of life and health status and (3) the effect of turbulent and episodic symptom profiles on personal identity and recovery.Conclusions The novel challenges presented by Long COVID are complex with varying inter-related factors that are broadly impacting functional status and quality of life. Support mechanisms must incorporate the lived experiences and foster true collaborations between health professionals, patients and researchers to improve patient outcomes.Trial registration number NCT04649957.